Co-cities : innovative transitions toward just and self-sustaining communities. - Foster, Sheila R. 1963-; Iaione, Christian (Cambridge, Massachusetts : The MIT Press, 2022)
"A new framework for experimental and innovative "city-making" for urban resources and services to be developed and governed in a collaborative, socially, and economically inclusive ways"--
Rethinking the city -- The urban commons -- The city as a commons -- Urban co-governance -- The co-city design principles -- Conclusion: New co-city horizons and challenges.
boek
Keywords: City planning; Civic improvement; Commons; Municipal government; Infrastructure (Economics); Public-private sector cooperation